Exercise training in heart failure: High-intensity interval training versus moderate-intensity continuous training - Raymond Pranata; Emir Yonas; Bambang Budi Siswanto; Budhi Setianto Purwowiyoto (International Journal of the Cardiovascular Academy, 2018)
Prevalence of heart failure (HF) increases over time and is associated with high mortality. Shortness of breath, exercise intolerance, and low quality of life related to health are the common problems in HF patients despite optimum pharmacological therapy. Exercise training counteracts the progression of devastating compensatory mechanisms of HF, leading to improvement in functional capacity and quality of life. Resistance training improves peak oxygen uptake, quality of life, and walking performance in HF patients. Adherence is central to training for the best result. Any exercise training program whether continuous or interval training is sufficient to improve the prognosis, quality of life, and anatomic function.